a^2 = (7±√13)/2
Now it gets tricky:
7+√13 = (1+2√13+13)/2 = (1+√13)^2/2
a^2 = (7+√13)/2 = (1+√13)^2/4
a = ±1/2 (√13+1)
a = ±1/2 (√13-1)
Makes things kind of nasty, the factors are
1/16 (±2x + √13 ± 1)
where all 4 combinations of + and - are used.
substitute u=a^2, then
and try to factorize.
However, check you question to see if there is a typo. The above expression in u does not have rational factors.
Answer this Question
math - If the sides of a box all double in length, by how much does its volume ...
Math - Use the Factor Theorem to determine whether x-3 is a factor of P(x)=2x^3-...
stats - two factor ANOVA indep measures exper. 2 level factor A 3 level factor B...
math - Is 3 a factor of 261? Is 10 a factor of 325? Is 6 a factor of 492?
Math - Factor Completely: I am really confused on how to start it. 12q^5w^2-36q^...
math - The graph of f (x)₌√x undergoes a vertical stretch by a ...
Factor - How do I factor these: 2x2 - 16x + 30 4x^2-9 x^2-5x 5x^2-26x+5 25x^2+4 ...
factoring - how to factor x^4 - 2x^3 - 8x + 16 Thanks. you can factor by ...
Math finance - I just brought a finanical calculator and i don't really know how...
Using the factor Theorem - use the factor theorem to determine whether x-c is a ...